Investigations on acceptor (Pr3+) and donor (Nb5+) doped cerium oxide for the suitability of solid oxide fuel cell electrolytes - Bhabu, K.A.; Theerthagiri, J.; Madhavan, J.; Balu, T.; Rajasekaran, T.R.; Arof, Abdul Kariem (Springer Verlag, 2016)
Nanocrystalline acceptor (Pr3+) and donor (Nb5+) doped cerium oxide are synthesized by sol-gel method via hydrolysis process and evaluated for the suitability of applying as an electrolyte for the intermediate temperature solid oxide fuel cells. Phase purity and crystallite size of the synthesized materials are ascertained by powder X-ray diffraction studies. Introduction of Pr3+ions in the cerium lattice exhibited a lower crystallite size than the Nb5+, which exposes the probability to attain high oxide ion conductivity of Pr3+doped cerium oxide. Fourier transform infrared and Raman spectra confirm the functional groups and formation of Pr3+and Nb5+ions in the cerium lattice. Absorbance spectra exhibit the charge-transfer transition from O2−(2p) to Ce4+(4f) orbital in cerium oxide. Pr3+and Nb5+ions doped cerium lattice create the oxygen vacancies and favor the formation of Ce3+from Ce4+. Valence band transition of Ce3+ions from the 5d to 4f levels are examined by photoluminescence studies. The morphological features of Ce-Pr-O and Ce-Nb-O are investigated by scanning and transmission electron microscopy. Electrochemical impedance spectroscopy is used to analyze the conductivity properties of solid electrolytes. Ce-Pr-O shows the high oxide ion conductivity of 0.1 S/cm at 600 °C with an activation energy of 0.73 eV. Electrolytes with specific conductivities higher than 10−2 S/cm at intermediate temperatures (∼400–600 °C) are required for solid oxide fuel cells to operate with less maintenance. Hence, Ce-Pr-O can be a suitable electrolyte material for intermediate temperature solid oxide fuel cells.